Association of handgrip strength with new-onset CKD in Korean adults according to gender - Lee, Sung-Bum; Kim, Miryung; Lee, Hui-Jeong; Kim, Jong-Koo (Frontiers in Medicine, 2023)
Introduction: Handgrip strength (HGS) is an indicator of many diseases such as pneumonia, cardiovascular disease and cancer. HGS can also predict renal function in chronic kidney disease (CKD) patients, but the value of HGS as a predictor of new-onset CKD is unknown. Methods: 173,195 subjects were recruited from a nationwide cohort and were followed for 4.1 years. After exclusions, 36,838 participants remained in the final study, and CKD developed in 388 individuals during the follow-up period. Lifestyle, anthropometric and laboratory data were evaluated in relation to the risk of CKD. Results: The participants were subdivided into quartiles according to relative handgrip strength (RGS). Multivariate Cox regression demonstrated that RGS was inversely associated with incident CKD. Compared with the lowest quartile, the hazard ratios (HRs) [95% confidence intervals (CIs)] for incident CKD for the highest quartile (Q4) was 0.55 (0.34 – 0.88) after adjusting for covariates in men and 0.51 (0.31 – 0.85) in women. The incidence of CKD decreased as RGS increased. These negative associations were more significant in women than in men. The receiver operating characteristic (ROC) curve showed that baseline RGS had predictive power for new-onset CKD. Area under the curve (AUC) (95% CIs) was 0.739 (0.707 – 0.770) in men and 0.765 (0.729 – 0.801) in women. Conclusions: This is the first study demonstrating that RGS is associated with incident CKD in both men and women. The relationship between RGS and incident CKD is more significant in women than in men. RGS can be used in clinical practice to evaluate renal prognosis. Regular measurement of handgrip strength is essential to CKD detection.